Anesthetics as chemical tools to study the structure and function of nicotinic acetylcholine receptors - Arias, Hugo Rubén (2005)
The nicotinic acetylcholine receptor (AChR) is the archetype of the Cys-loop ligand-gated ion channel'receptor superfamily. Noncompetitive antagonists inhibit the AChR without interacting directly with agonist sites. Among non-competitive antagonists, general and local anesthetics have been used for decades to study the structure and function of muscle- as well as neurorial-type AChRs. In this review, we address and update all information regarding the characterization of binding sites and the mechanism of action for n-alkanols, barbiturates, inhalational and dissociative general anesthetics, as well as for tertiary and quaternary local anesthetics. The experimental evidence outlined in this review suggest that: (1) several neuronal-type AChRs might be targets for the pharmacological action of distinct anesthetics; (2) the molecular components of a specific anesthetic locus on a certain receptor type are different from the structural determinants of the site for the same anesthetic on a different receptor type; (3) there are unique binding sites for distinct anesthetics in the same receptor; (4) the affinity of a specific anesthetic depends on the AChR conformational state; (5) anesthetics may inhibit AChRs by different mechanisms including open-channel-blocking, augmenting the desensitization process, and/or inactivating the opening of resting receptors; and (6) some anesthetics may potentiate AChR activity.